KONTRIBUSI TANDAN KOSONG DALAM MENINGKATKAN PENGARUH PUPUK ANORGANIK TERHADAP PRODUKSI KELAPA SAWIT - Suprih Wijayani; Herry Wirianata (Program Studi Agroteknologi INSTIPER, 2022)
Sustainable intensification of oil palm plantations faces the challenge of decreasing soil fertility and increasing the price of inorganic fertilizers. Organic matter plays an important role in maintaining soil fertility. Empty fruit bunches (EFB) are the main co-product of palm oil mills that have the potential to be used as a source of organic matter and nutrient sources. This study aims to reveal the effect of the application of empty fruit bunches in increasing the effectiveness and substituting inorganic fertilizers for the components of oil palm production. The number of female inflorescence, the number of FFB and the average weight of FFB were observed for 3 years on palm aged 8, 9 and 10 years. Application of EFB + 70% recommended inorganic fertilizer. The recommended fertilizer is 8 kg per tree (N P K Mg 14-28-6-2 +0.5 B). EFB are applied as one layer of mulch with a size of 3x4 m on a dead net. The results showed that the application of empty bunches could increase the number of female flowers and the number of FFB in plants aged 9 and 10 years (1-2 years after application), while inorganic fertilizer EFB was only at the age of 8 years (0 years after application) for both production components. FFB weight one year after application of EFB+70% inorganic fertilizer (age 9 years ) was higher than 8 and 10 year aged plants. The application of EFB+70% inorganic fertilizer can increase the contribution of nutrients from fertilizers compared to the application of inorganic fertilizers solely.